Mediation Practices in Post-Conflict Situation in Nepal: The Way Forward - Pant, Sambid Bilas (Social Inquiry: Journal of Social Science Research, 2020)
This paper aims to critically examine the increasing role of community mediation in the post-conflict situation in Nepal. The practice of community mediation at the professional level is in a preliminary stage in Nepal. Regardingthe peace settlement process and the state of community mediation in different countries, various efforts have been made in Nepal regarding community mediation. The country is gradually advancing towards community mediation practices in ensuring access to justice. Community mediation has been practiced for resolving disputes or conflict through the judicial committees (JCs) formed under the local government. The practices of conflicts or disputes resolution through community mediation have begun in Nepal at the individual or family level, school or community level, or at workplace. It is, therefore, vital to prevent the recurrence of conflicts or disputes through community mediation to ensure sustainable peace. Various efforts have been made to build the capacity of individuals and agencies to settle disputes and to ensure mutual trust and cooperation in Nepal. In the changing context, confronting COVID 19, building awareness, providing education and training to the mediators for community mediation is vital to execute JC practice in Nepal. Community mediation as an important aspect in ensuring sustainable peace in the spirit of the local government act is, therefore, very essential in Nepal.